1999
DOI: 10.1524/ract.1999.86.34.79
|View full text |Cite
|
Sign up to set email alerts
|

Angular Momentum Effects on Mass Division in Actinide Fission

Abstract: Angular momentum (/) effects on mass yield curves were studied for the fission from the same compound nucleus (CN) 239 Np of the same excitation energy but with different angular momenta, produced by the 7 Li+ 232 Th and p+ 2M U reactions. The effects were examined only for the complete fusion-fission events after careful estimation of the contribution of incomplete fusion-fission. It is found that the width of the whole mass yield curve is larger while the peak-to-valley ratio is smaller for the 7 Li+ 232 Th … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
(43 reference statements)
1
4
0
Order By: Relevance
“…This analysis indicates that the magnitude of transfer induced fission may be small. This is consistent with the observation of Zhao et al [9]. PACE2 code was also used to calculate the complete fusion fission cross section (CFF) and cross sections of evaporation residues formed following complete fusion.…”
Section: Mass Distribution In 366 and 314 Mev 7 LI Induced Fission supporting
confidence: 87%
See 3 more Smart Citations
“…This analysis indicates that the magnitude of transfer induced fission may be small. This is consistent with the observation of Zhao et al [9]. PACE2 code was also used to calculate the complete fusion fission cross section (CFF) and cross sections of evaporation residues formed following complete fusion.…”
Section: Mass Distribution In 366 and 314 Mev 7 LI Induced Fission supporting
confidence: 87%
“…The mass distribution is asymmetric, which is typical of low energy fission of actinides. Zhao et al [9] have also reported the asymmetric mass distribution in 7 Li induced fission of 232 Th at similar excitation energies. In order to extract the total fission cross section, the cumulative yields of various mass chains were fitted as sum of two Gaussians.…”
Section: Mass Distribution In 419 Mev 7 LI Induced Fission Of 232 Thmentioning
confidence: 83%
See 2 more Smart Citations
“…6. Cross sections of the following reactions: a) 238 U( p, 3n) 236m Np (1), 238 U( p, n) 238 Np β − −→ 238 Pu (2) and 238 U( p, 3n) 236m Npβ − −→ 236 Pu (3)[7,8]; solid and dashed lines are polynomial fits of the experimental cross sections; crosses and triangles are from[25], diamonds -from[33]; b) 236 U( p, n) 236m Np (1), 236 U( p, 2n) 235 Np (2) and 236 U( p, 3n) 234 Np (3)[4,5]; solid lines are results of the theoretical calculations from[4]; c) 237 Np( p, 2n) 236 Pu (1) and 237 Np( p, pn + d) 236m Np (2); circular and rombic points were derived in work[9], E p = 10.9-17.5 MeV; squared and triangular points are from[10], E p = 15.9-39.6 MeV; solid lines are spline fits of experimentally determined cross sections; d)237 Np( p, n) 237 Pu (1) and 237 Np( p, 2n + pnβ − + dβ − ) 236 Pu (2); circular and rombic points were derived in work[9], E p = 10.9-17.5 MeV; squared and triangular points are from[10], E p = 15.9-39.6 MeV; solid lines are spline fits of experimentally determined cross sections; e) 237 Np( 3 He, 4nε + p3n + 2 p2nβ − ) 236 Pu (1), 237 Np( 3 He, 3nε + p2n) 237 Pu (2) and 237 Np( 3 He, 2nε + pn + 2 pβ − ) 238 Pu (3)[4,5,11,12]; solid lines are polynomial fits of the experimental cross sections; f) 236 U( 3 He, t) 236m Np (1), 236 U( 3 He, p3n) 235 Np (2) and 236 U( 3 He, p4n) 234 Np (3) [6, 14 and this work]; solid lines are polynomial fits of the experimental cross sections; g) 236 U( 3 He, n + pβ − ) 238 Pu (1) and 236 U( 3 He, p2nβ − ) 236 Pu (2)[6,14]; solid lines are polynomial fits of the experimental cross sections; h) 236 U( 3 He, 2n) 237 Pu; solid line is polynomial fit of the experimental cross sections[6,14].…”
mentioning
confidence: 99%